Severe chronic active Epstein-Barr virus infection syndrome. - Okano, M (1991)
Reports of unusually severe lymphoproliferative disorders associated with extremely high antibody titers against Epstein-Barr virus (EBV) have recently increased. The syndrome, which we designated severe chronic active EBV infection syndrome, is characterized by persistent or intermittent fever, lymphadenopathy, and hepatosplenomegaly and primarily affects children and young adults. Polyclonal gammopathy and bone marrow suppression are generally observed, and some patients develop B-cell or T-cell lymphoproliferation or lymphoma. Frequently, EBV genomes are detectable in tissues infiltrated with lymphoid cells. Additionally, it is difficult to establish spontaneous or B95-8 EBV-induced cell lines despite the expression of an activated EBV infection. We review and report here the published medical literature and our own experience regarding patients with severe chronic active EBV infection syndrome in an attempt to understand this enigmatic syndrome and the possible pathogenetic mechanism(s) responsible for this disorder.